Influence of Resource Availability on Disability-inclusion in Under-resourced Early Childhood Development Centers - Musengi, Esther (Journal of the American Academy of Special Education Professionals, 2024)
This study analyzed the influence of resource availability on inclusion of children with various disabilities in rural early childhood development centers in Zimbabwe. A qualitative descriptive design utilizing questionnaires and interviews was used to collect data from 36 teachers, 12 school-heads and 24 parents of children with disabilities who were purposefully sampled. Deductive thematic analysis was used to identify themes emerging from open-ended questionnaire items and interviews. The study revealed that disability-friendly commercial resources were unavailable, and this negatively influenced the inclusion of children with disabilities who were unable to freely participate in play activities and so were isolated to a large extent. This is despite widely available indigenous resources that were not utilized as inclusive supports. The study’s findings are utilized to build a case for a heritage-based model of inclusive education.